KEPEMIMPINAN KEPALA MADRASAH DALAM MENGIMPLEMENTASIKAN PROJEK PENGUATAN PROFIL PELAJAR PENCASILA (P5) RAHMATAN LIALAMIN Pada Madrasah Nurul Ulum Teluk Tiram Darat Banjarmasin - Achmad Fauzi (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study aims to find out about the implementation of the Rahmatan Lil Alamin Pancasila Student Profile Strengthening Project carried out by the Principal of Madrasah Nurul Ulum Te-luk Tiram Darat Banjarmasin. The implementation steps are: (First) The Principal of Madrasah as a visionary madrasah, forms a learning committee, namely a team at Madrasah Nurul Ulum consisting of several teachers selected by the principal to design the KOM doc-ument including designing the Pancasila Student Profile Strengthening Project. Rahmatan Lil Alamin. (Second) The Principal of Madrasah Holds an IHT on the Independent Curriculum and the preparation of KOM including the IHT for the Pancasila Student Profile Strengthen-ing Project. (P5). (Third) The Principal of Madrasah together with the teachers forms and se-lects a team of facilitators and the Project Coordinator for Strengthening the Pancasila Stu-dent Profile Rahmatan Lil Alamin (P5. consisting of teachers whose subjects are integrated in the project theme and module. (Fourth). The Principal of Madrasah together with the teachers selects the project theme and dimensions of the Rahmatan Lil Alamin Pancasila Student Profile Strengthening Project (P5). The selection of the P5 theme is carried out in a small meeting with the project team, and several teachers, including all students involved. (Fifth) The principal together with the teacher determines the implementation time, after the P5 topic is prepared, the next step is to determine the implementation time, and design the time allocation for the Rahmatan Lil Alamin Pancasila Student Profile Strengthening Project and identify the total number of project hours in one week (Sixth). The principal together with the teacher compiles and develops the Rahmatan Lil Alamin Pancasila Student Profile Strengthening Project module. The development of the project module is a step in compiling the final report of the Rahmatan Lil Alamin P5 activity carried out by the madrasa project team and students.